Sagot :
Answer:
Changes made to your input should not affect the solution:
(1): "b2" was replaced by "b^2".
Step by step solution :
STEP
1
:
Trying to factor by splitting the middle term
1.1 Factoring b2-4b-5
The first term is, b2 its coefficient is 1 .
The middle term is, -4b its coefficient is -4 .
The last term, "the constant", is -5
Step-1 : Multiply the coefficient of the first term by the constant 1 • -5 = -5
Step-2 : Find two factors of -5 whose sum equals the coefficient of the middle term, which is -4 .
-5 + 1 = -4 That's it
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -5 and 1
b2 - 5b + 1b - 5
Step-4 : Add up the first 2 terms, pulling out like factors :
b • (b-5)
Add up the last 2 terms, pulling out common factors :
1 • (b-5)
Step-5 : Add up the four terms of step 4 :
(b+1) • (b-5)
Which is the desired factorizatio
2. answer =0
2. (5b)(b²–4b+2)
= 5b³–20b²+10b
3. (-3m²)(4m–6)
= -12m³+18m²
4. (-2x)(2x²+x–4)
= -4x³–2x²+8x
= 5b³–20b²+10b
3. (-3m²)(4m–6)
= -12m³+18m²
4. (-2x)(2x²+x–4)
= -4x³–2x²+8x